2021
DOI: 10.1080/26410397.2021.1890868
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences using drugs to induce abortion acquired in the informal sector in Colombia: qualitative interviews with users in Bogotá and the Coffee Axis

Abstract: In 2006, abortion in Colombia was decriminalised under certain circumstances. Yet some women continue to avail themselves of ways to terminate pregnancies outside of the formal health system. In-depth interviews (IDIs) with women who acquired drugs outside of health facilities to terminate their pregnancies (n = 47) were conducted in Bogotá and the Coffee Axis in 2018. Respondents were recruited when they sought postabortion care at a health facility. This analysis examines women's experiences with medication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…21 22 Others show that even when misoprostol is available contributing to decrease abortion-related complications, barriers on accessing information on use, dosage and expected outcomes make women misinterpret warning signs affecting when to seek care. [23][24][25] Even though the participating numbers were small, women's responses in the ACASI exit survey showed that 46% did not have any previous information on how to end a pregnancy. 26 27 Among those who stated having some information, friends and physicians were the most frequently reported source.…”
Section: Discussionmentioning
confidence: 99%
“…21 22 Others show that even when misoprostol is available contributing to decrease abortion-related complications, barriers on accessing information on use, dosage and expected outcomes make women misinterpret warning signs affecting when to seek care. [23][24][25] Even though the participating numbers were small, women's responses in the ACASI exit survey showed that 46% did not have any previous information on how to end a pregnancy. 26 27 Among those who stated having some information, friends and physicians were the most frequently reported source.…”
Section: Discussionmentioning
confidence: 99%
“…Many pregnant people have cited mistreatment by health practitioners, denial of services, and fear of being reported to the police, as barriers to legal abortions. 1 Recent evidence suggests that barriers to abortion care have deepened throughout the pandemic. 2 Mobility restrictions introduced by the government in response to COVID-19 resulted in more pregnant people delaying their abortions.…”
Section: Introductionmentioning
confidence: 99%
“…The Guttmacher Institute has used qualitative inquiry as a systematic approach to understanding the social and cognitive processes that drive people's sexual and reproductive health (SRH) behaviors and outcomes for decades [47][48][49][50]. The Qualitative Transparency checklist was developed as a part of a larger initiative at the Guttmacher Institute to begin incorporating reproducible practices into its quantitative workflows and publicly sharing the data and code that underlie its quantitative analyses.…”
Section: Results: Developing and Using The Checklistmentioning
confidence: 99%